Intellectual Property and Development - Olwan, Rami M. author. aut Link
XX, 392 p.
Keywords: The book examines the correlation between Intellectual Property Law – notably copyright – on the one hand and social and economic development on the other. The main focus of the initial overview is on historical, legal, economic and cultural aspects. Building on that, the work subsequently investigates how intellectual property systems have to be designed in order to foster social and economic growth in developing countries and puts forward theoretical and practical solutions that should be considered and implemented by policy makers, legal experts and the Word Intellectual Property Organization (WIPO).